RESPONS PESERTA DIDIK TERHADAP BAHAN AJAR E-MODUL BERBANTUAN APLIKASI CANVA PADA PEMBELAJARAN TEKS FABEL KELAS VII SMP - Rahma Tiara Iswandi; Ika Mustika; Restu Bias Primandika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Fable text learning is studied at the SMP level which conveys a picture of human behavior and mind played by animals. Based on the observation of experience that has been done, thisrresearch is motivateddby the limitedduse of teachinggmaterials in classsVII fable texts. Observations in the field found that the teaching materials used were only based on textbooks. This is due to the limitations of the projector in the class. Thus, the purposeewas to find out students' responsessto e-moduletteaching materials assisted by the Canva application in class VII fable text learning. The methoddused is a qualitativeemethod with a descriptiveeapproach. The data collectionntechniqueuused is by providing questionnaires to find out student respondents to teaching materials. The questionnaire consists of 10 statements covering the use of teaching materials, the ease and difficulty of providing e-modules. The population to be taken is class VII students with a total of 28 students' questionnaire assessment using a Likert scale guide 1-4. Based on the resultssof data processinggin thissstudy, student respondents in learning to write fable text using e-moduletteaching materials assisted by the Canvaaapplication received good responses from students SMP 3 Batujajar in class VII.